2011
DOI: 10.1088/0957-4484/22/28/285609
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on electrospinning of nanobelts: the case of hafnium oxide

Abstract: Electrospinning is a convenient and versatile method for fabricating different kinds of one-dimensional nanostructures such as nanofibres, nanotubes and nanobelts. Environmental parameters have a great influence on the electrospinning nanostructure. Here we report a new method to fabricate hafnium oxide (HfO(2)) nanobelts. HfO(2) nanobelts were prepared by electrospinning a sol-gel solution with the implementation of heating and subsequent calcination treatment. We investigate the temperature dependence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The whole preparation can be segmented into electrospinning and heat treatment. Based on the earlier researches, one can be summarized that the novel ribbon-like structure of SrFe 12 O 19 nanoribbons is produced during electrospinning process 25 35 36 37 38 . When the spinning solution arrived up to the spinneret tip, a Taylor-cone shape colloidal droplet ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The whole preparation can be segmented into electrospinning and heat treatment. Based on the earlier researches, one can be summarized that the novel ribbon-like structure of SrFe 12 O 19 nanoribbons is produced during electrospinning process 25 35 36 37 38 . When the spinning solution arrived up to the spinneret tip, a Taylor-cone shape colloidal droplet ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other methods, electrospinning possesses many advantages, such as large-area preparation, on both conductive and insulating substrates, and cost-effective. It is reported that different nanostructures, for example, nanofibers [17], nanotubes [18] and nanobelts [19] have been fabricated by electrospinning technique. Here, we report the preparation of highly transparent nanocrystalline TiO 2 films by electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as ambient factors, the function of temperature and humidity influence the fiber morphology as well [68,69]. Thus, in order to obtain a stable condition during the spinning process, an environmental chamber is ideal [70].…”
Section: The Electrospinning Principle and Processingmentioning
confidence: 99%